Ungrading : why rating students undermines learning (and what to do instead) - Blum, Susan Debra; Kohn, Alfie (Teaching and learning in higher education (West Virginia University Press), 2020)
"The moment is right for critical reflection on what has been assumed to be a core part of schooling. In Ungrading, fifteen educators write about their diverse experiences going gradeless. Some contributors are new to the practice and some have been engaging in it for decades. Some are in humanities and social sciences, some in STEM fields. Some are in higher education, but some are the K-12 pioneers who led the way. Based on rigorous and replicated research, this is the first book to show why and how faculty who wish to focus on learning, rather than sorting or judging, might proceed. It includes honest reflection on what makes ungrading challenging, and testimonials about what makes it transformative"